Islamic Financial Product Development: Shariah Analysis - Abdullaah Jalil (IIiBF, 2010)
Islamic banking and financial institutions should be able to foresee the needs of the market and roll out Islamic financial products and services in advance of conventional products to ensure constant growth and competitiveness of Islamic banking and financial products. However, Islamic banking and financial products and services tended to duplicate the conventional ones, resulting in these products losing value and causing some confusion in their interpretation. Hence, it is essential for the Islamic financial institutions to move beyond the adaptation of conventional products and stimulate new ideas that will help the Islamic banking and financial industry nourish. The subject of Islamic financial product development covers various aspects of studies. However, this study aims to analyze the Shariah aspect of Islamic financial product development and discuss the issues arise in the process based on secondary resources. The output of this study should contribute to the advancement of procedure for Islamic financial product development, particularly from the Shariah aspect, as it is the most imperative tool for the Islamic financial institutions to meet their increasing concern about profitability, liquidity, assets value, risk management as well as product acceptability. The study proves that fiqh muamalat discipline provides ample spaces for developing Islamic product development, an area in which Islamic financial institutions should focus their resources.